Kegiatan Anak Putus Sekolah di Kampung Maredan Barat Kecamatan Tualang Kabupaten Siak - Yuda Perkasa Barus; Said Suhil Achmad; Muhammad Jais (LPPM Institut Nasional Laa Roiba Bogor, 2023)
This study is directed to review and analyze the activities of school dropouts in Kampung Maredan Barat. Descriptive approach as well as qualitative methods are used in this study. In this study, 3 out of school children were used as informants. This study uses data collection techniques of observation, interviews, and documentation. Data analysis in this study was carried out by collecting data, reducing data, presenting data, and drawing conclusions. Triangulation is done to explain the validity of the data by triangulating sources. The results of this study show that the activities of children dropping out of school in Kampung Maredan Barat, Tualang, Siak are seen from work indicators. School dropouts have activities that are beneficial for their families. In order to help and fulfill the needs of their families, they are willing to work their daily activities working in workshops and palm oil workers, in addition to their hobby, they participate in Jaran Kepang activities. In addition, there are those who work not because they want to meet the needs of their families, the activities they do to earn income and can learn from outside, because they are unable to receive knowledge at school. This child carries out activities to help parents at home sweeping and washing dishes, helping to care for his father's fields, as well as working as a construction worker and activities for school dropouts in Maredan Barat Village, Tualang, Siak seen from the play indicators. School dropouts have activities that are only concerned with themselves and do not care about the views of their environment or family. Playing activities that they do such as playing games at home, stalls, gardens, in addition to playing games, they do activities according to their hobbies, namely Jaranan Kepang art activities. Keywords: School Dropout Activities